Progression patterns under BRAF inhibitor treatment and treatment beyond progression in patients with metastatic melanoma - Hassel, Jessica C.; Buder-Bakhaya, Kristina; Bender, Carolin (Cancer medicine, 2018)
Despite markedly improved treatment options for metastatic melanoma, resistance to targeted therapies such as BRAF inhibitors (BRAFi) or BRAFi plus MEK inhibitors (MEKi) remains a major problem. Our aim was to characterize progression on BRAFi therapy and outcome of subsequent treatment. One hundred and eighty patients with BRAF-mutant metastatic melanoma who had progressed on treatment with single-agent BRAFi from February 2010 to April 2015 were included in a retrospective data analysis focused on patterns of progression, treatment beyond progression (TBP) and subsequent treatments after BRAFi therapy. Analysis revealed that 51.1% of patients progressed with both new and existing metastases opposed to progression of only preexisting (28.3%) or only new (20.6%) metastases. Exclusive extracranial progression occurred in 50.6% of patients compared to both extra- and intracranial (29.4%) or sole cerebral progression (20%). Multivariable analyses demonstrated that single site progression and primary response to BRAFi were associated with improved progression-free survival. Progression with exclusively new or only existing metastases and a baseline Eastern Cooperative Oncology Group (ECOG) of 0 were associated with prolonged overall survival (OS). TBP had no significant impact on OS. Other subsequent treatments showed low efficacy with the exception of anti-PD-1 antibodies. In conclusion we identified specific patterns of progression which significantly correlate with further prognosis after progression on BRAFi treatment. In contrast to previously published data, we could not demonstrate a significant survival benefit for BRAFi TBP. Subsequent therapies had strikingly low efficacy except for PD-1 inhibitors.